If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6 + -5x) = 3(7 + -5x) (6 * 4 + -5x * 4) = 3(7 + -5x) (24 + -20x) = 3(7 + -5x) 24 + -20x = (7 * 3 + -5x * 3) 24 + -20x = (21 + -15x) Solving 24 + -20x = 21 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 24 + -20x + 15x = 21 + -15x + 15x Combine like terms: -20x + 15x = -5x 24 + -5x = 21 + -15x + 15x Combine like terms: -15x + 15x = 0 24 + -5x = 21 + 0 24 + -5x = 21 Add '-24' to each side of the equation. 24 + -24 + -5x = 21 + -24 Combine like terms: 24 + -24 = 0 0 + -5x = 21 + -24 -5x = 21 + -24 Combine like terms: 21 + -24 = -3 -5x = -3 Divide each side by '-5'. x = 0.6 Simplifying x = 0.6
| [6m]=42 | | 3x+2(x+3)=4(2x-1)-5 | | 6-6x-4=-46+3x-15 | | 4(5x-6)=10x+12x-2x | | 8x+5=4(3x-2)-3 | | 21+1.5h=28-2h | | x^2-3xy+2y^2-y+x=0 | | 11-(2x+5)=-5x+7 | | x/3-1/2=1/2 | | 3+2(5x-4)=3(2x-3)+2x | | 13k+5=k-11 | | (33x)+(145y)=44000 | | (145x)+(33y)=44000 | | 7(3x-8)=5(4x-11) | | e/3=15 | | 36x^2+36x+9= | | 2m=16 | | 3x-5+x=8x+7 | | 1.3x=-7 | | (6x+19)-(14x+5)= | | .3x=-7 | | 17=4x+1-2x | | -n=30 | | 4x+22=22 | | (6x+14)-(9x+5)= | | 3,75100,000= | | y^2-12y+12=0 | | 13=9x+5-5x | | 2a+6+5a=3a-10 | | -12+.2x-.3x+x=6x | | d^5+5d-4=0 | | 6x^2=x+40 |